The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.15585/mmwr.ss6702a1
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance for Violent Deaths —
National Violent Death Reporting System, 18 States, 2014

Abstract: Problem/ConditionIn 2014, approximately 59,000 persons died in the United States as a result of violence-related injuries. This report summarizes data from CDC’s National Violent Death Reporting System (NVDRS) regarding violent deaths from 18 U.S. states for 2014. Results are reported by sex, age group, race/ethnicity, marital status, location of injury, method of injury, circumstances of injury, and other selected characteristics.Reporting Period Covered2014.Description of SystemNVDRS collects data from parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 15 publications
0
53
0
1
Order By: Relevance
“…Precipitating circumstances included the following: physical health problems (e.g., cancer, pain‐related conditions); civil legal problems; financial problems; job problems; and other relationship problems. These factors have been cited elsewhere as precipitating circumstances of homicide‐suicide (Bossarte et al., ; Fowler et al., ; Logan et al., ; Violence Policy Center, ) and risk factors for suicide (DeLeo et al., ). Other preceding circumstances included the following: current depressed mood; mental health conditions; alcohol problems; other substance abuse problems; alcohol use at the time of death based on the toxicology reports; current mental health or substance abuse treatment; history of mental health or substance abuse treatment; history of suicide attempts; disclosure of suicide intent; and leaving a note.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Precipitating circumstances included the following: physical health problems (e.g., cancer, pain‐related conditions); civil legal problems; financial problems; job problems; and other relationship problems. These factors have been cited elsewhere as precipitating circumstances of homicide‐suicide (Bossarte et al., ; Fowler et al., ; Logan et al., ; Violence Policy Center, ) and risk factors for suicide (DeLeo et al., ). Other preceding circumstances included the following: current depressed mood; mental health conditions; alcohol problems; other substance abuse problems; alcohol use at the time of death based on the toxicology reports; current mental health or substance abuse treatment; history of mental health or substance abuse treatment; history of suicide attempts; disclosure of suicide intent; and leaving a note.…”
Section: Methodsmentioning
confidence: 99%
“…Screening for IP problems in isolation of other predictors would greatly overestimate men at risk of perpetrating IP homicide‐suicide, even among men who have suicidal intentions. Therefore, it is challenging for clinicians, counselors, or even acquaintances to know when they should engage in reducing risk of IP homicide if they are concerned and monitoring risk of suicide (DeLeo, Bertolote, & Lester, ; Fowler, Jack, Lyons, Betz, & Petrosky, ; Knoll, ).…”
mentioning
confidence: 99%
“…The consequences of IPV are considerable and underscore the burden that this form of violence creates. The most severe consequence of IPV is death; data from the National Violent Death Reporting System (NVDRS) from 18 states in 2014 indicated that IPV was a precipitating factor in 48% of all homicides of females and in 9% of homicides of males (Fowler et al 2018). However, victims of IPV are not the only ones who are killed in incidents involving IPV.…”
Section: Introductionmentioning
confidence: 99%
“…A review of suicides in the Marshall Islands identified a commonality of alcohol and other illicit substance use at the time of the incident 13. From 1991 to 1995, the percent of alcohol-related suicides in the Marshall Islands averaged 68% but were as high as 83%, which is significantly higher than the general US population 26,27. The association between substance use and suicide in addition to underreporting of depressive symptoms, stigma, and beliefs may have significant implications for the Marshallese population.…”
Section: Discussionmentioning
confidence: 96%